Arteries Stiffen With Age, but Can Retain an Ability to Become More Elastic With Applied External Cuff Pressure. Issue 41 (October 2015) - Liu, Chengyu; Zheng, Dingchang; Murray, Alan
Abstract : Abstract: It is accepted that arterial compliance decreases with age, with changes in the arterial pulse shape measured at the periphery. The aim of this study was to determine the relationship between arterial transmural pressure changes and changes in peripheral finger pulse shape characteristics for both older and younger subjects. Finger photoplethysmographic pulses were recorded noninvasively from the right index fingers of 100 healthy normotensive subjects. Their median age was 43 years (range 20–71 years) allowing two distinct age groups to be compared (older group ≥45 and younger group < 45 years). Arterial transmural pressures on the whole right arm were reduced with a 50 cm long cuff inflated to 10, 20, 30, and 40 mmHg. Pulse maximum amplitude and rise time were calculated for each age group, and for each cuff pressure level. Gradual and significant decreases in both pulse maximum amplitude and rise time were found with increasing cuff pressure for both age groups. With an external cuff pressure of 40 mmHg, there was an average maximum amplitude and rise time decrease of 27.1% ( P < 0 .001) and 7.5% ( P < 0 .001) respectively. The changes in the older group were significantly greater than those in the younger group for maximum amplitude (30.3% vs 24.4%, P = 0 .006), but not for rise time (8.0% vs 6.7%, P = 0 .23). Our results show that arterial compliance of the arm artery increases with reduced transmural pressure for both older and younger groups, and demonstrate that the aged arm artery can become more elastic with applied external cuff pressure.